(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article examines the concept of the monomyth as one of the key theoretical models in comparative mythology and narratology of the twentieth and twenty-first centuries. It analyzes the origin of the term, its conceptual content in the works of J. Campbell, as well as the structural model of the “hero’s journey.” Particular attention is paid to the theoretical foundations of the monomyth concept associated with C. G. Jung’s analytical psychology and A. van Gennep’s anthropology of ritual, as well as to the main lines of criticism of this model in contemporary humanities scholarship. The article concludes by emphasizing the functional significance of the monomyth as an analytical tool in literary studies and mythological discourse.